2020
DOI: 10.1016/j.semarthrit.2020.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of COVID-19 in a cohort of adult and paediatric patients with rheumatic diseases treated with targeted biologic and synthetic disease-modifying anti-rheumatic drugs

Abstract: To investigate the incidence of COVID-19 in a cohort of adult and paediatric patients with rheumatic diseases receiving targeted biologic and synthetic disease modifying anti-rheumatic drugs (tDMARDs) and to explore the possible effect of these treatments in the clinical expression of COVID-19. Methods: A cross-sectional study comprising of a telephone survey and electronic health records review was performed including all adult and paediatric patients with rheumatic diseases treated with tDMARDs in a large rh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
113
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(126 citation statements)
references
References 27 publications
11
113
1
1
Order By: Relevance
“…Additionally, a large portion of our cohort of infected patients (n = 13) was frequently hospitalized (61.5%) and had a high mortality rate (23.1%). Few studies have described SARS-CoV-2 infection among RMD patients and those that undergo immunosuppressive treatments, but all of them have reported lower hospitalization and death rates compared to our patients, with mortality ranging between 0 and 10% [4][5][6][11][12][13]. However, given the small number of patients in these studies, very few have analyzed specific risk factors related to immunosuppressive therapies, and most of them have reported higher hospitalization rates for patients receiving chronic glucocorticoids compared to those not receiving them [4,6,8].…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…Additionally, a large portion of our cohort of infected patients (n = 13) was frequently hospitalized (61.5%) and had a high mortality rate (23.1%). Few studies have described SARS-CoV-2 infection among RMD patients and those that undergo immunosuppressive treatments, but all of them have reported lower hospitalization and death rates compared to our patients, with mortality ranging between 0 and 10% [4][5][6][11][12][13]. However, given the small number of patients in these studies, very few have analyzed specific risk factors related to immunosuppressive therapies, and most of them have reported higher hospitalization rates for patients receiving chronic glucocorticoids compared to those not receiving them [4,6,8].…”
Section: Discussionmentioning
confidence: 57%
“…COVID-19 severity ranges from asymptomatic to severe, and the disease can result in acute respiratory distress syndrome (ARDS) and cytokine storm, which have led to death in 3-10% of the infected population. Patients with rheumatic and musculoskeletal diseases (RMDs) are at high risk for infections related to their disease, comorbidities, or immunosuppressive treatments [3], but recent studies regarding COVID-19 did not support higher mortality in these patients [4][5][6][7]. However, there are few data regarding specific risk factors for unfavorable outcomes, such as specific diseases or immunosuppressive drugs [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We read with great interest the study by Michelena et al [1] investigating the incidence of the Coronavirus 19 disease (COVID-19) among adult and pediatric patients with rheumatic disease receiving anti-rheumatic drugs. They found an incidence rate comparable with general populations and they did not observe an increased risk of severe COVID-19.…”
mentioning
confidence: 99%
“…3 Patients with systemic RMD had similar rates of COVID-19 compared with the general population according to several reports. [7][8][9] In contrast, patients with RMD had a higher prevalence of PCR-confirmed COVID-19 compared with the reference population (0.76% vs 0.58%, OR=1.32, 95% CI 1.15 to 1.52) in a Spanish study. 10 However, that study only identified patients presenting to emergency departments, and patients with a milder disease were not included.…”
mentioning
confidence: 79%